Characterization of physics and astronomy assistant professors’ reflections on their teaching: can they promote engagement in instructional change? - Haleigh Machost; Emily A. Kable; Jherian K. Mitchell-Jones; Brandon J. Yik; Marilyne Stains (Disciplinary and Interdisciplinary Science Education Research, 2024)
Abstract The development of reflective practitioners is one of four dominant change strategies in the Science, Technology, Engineering, and Mathematics (STEM) higher education literature. However, little research concerns the characterization of faculty’s reflections. Before professional development programs can effectively incorporate reflective writings as a tool for pedagogical improvement, it is necessary to first understand the current state of faculty’s reflections. To accomplish this goal, 98 physics and astronomy instructors were recruited from a teaching-focused professional development workshop and were asked to write a reflection on a self-identified challenging teaching experience. A combination of a priori coding to analyze the content and depth of the reflections, as well as in vivo coding to better capture instructors’ thinking were utilized. The majority of instructors wrote low-level reflections, wherein connections were not made between an instructors’ actions and the observed outcomes or the described experience was not centered on students’ outcomes or educational research literature. Approximately half of the instructors contemplated their own growth and the relationships with their students. However, only a small minority of instructors considered larger societal, cultural, or ethical factors. Plans created by instructors to address future, similar situations heavily relied on the instructors themselves, regardless of the depth of their reflections, and few planned to seek out knowledge from other resources such as peers or the education literature. This study indicates that instructors may not engage in the types of reflection that are considered to promote meaningful instructional change. Trends in the instructors’ plans show that ongoing support is necessary for them to effectively reflect and grow as practitioners. Overall, this work provides valuable insight into the poorly understood nature of faculty’s reflections and showcases the need for more research to fully characterize reflections across STEM disciplines and to better inform professional development.